A two-dimensional nanosheet MN X -C catalyst and its preparation method and application

By preparing efficient two-dimensional M-NX-C catalysts, the problem of Li2CO3 accumulation in lithium-carbon dioxide batteries is solved, the cycle life and electrochemical performance of the battery are improved, and the battery performance with low overpotential and high specific capacity is achieved.

CN116845258BActive Publication Date: 2025-03-25TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310568086.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-19
Publication Date
2025-03-25
Estimated Expiration
2043-05-19

AI Technical Summary

Technical Problem

The accumulation of the insulating discharge product Li2CO3 produced by lithium-carbon dioxide batteries during the redox reaction affects the reversibility of the reaction and the cycling performance of the battery, resulting in slow reaction kinetics, high overpotentials, severe polarization and poor reversibility.

Method used

Using the preparation method of two-dimensional ZIFs-derived materials, ZIFs are grown in situ by reacting metal salts in anhydrous methanol with nitrogen heterocyclic organic ligands, and then silicon hard template coating, carbonization assembly and template etching are carried out to prepare an efficient M-NX-C bifunctional catalyst.

Benefits of technology

It improves the electrochemical performance of lithium-carbon dioxide batteries, reduces the overpotential, extends the cycle life, enhances the contact between the catalyst and the electrolyte, reactants and intermediates, and improves the absorption-desorption capacity of CO2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116845258B_ABST
    Figure CN116845258B_ABST
Patent Text Reader

Abstract

The present invention discloses a two-dimensional nanosheet M-N X The preparation method of the catalyst is related to the technical field of lithium-gas battery electrode material preparation. The metal salt is mixed with nitrogen heterocyclic organic ligands using anhydrous methanol as a medium, and the in-situ growth-template confinement-carbonization assembly is performed to form a highly nitrogen-doped M-N X ‑C two-dimensional nanomaterials; the prepared two-dimensional nanosheets are cross-interconnected, which can shorten the electron transmission path and enhance the electron-proton transfer capacity; the large specific surface area and high stability increase the effective contact between the catalyst and the electrolyte, reactants and intermediates; the strong coupling interface between the transition metal and the nitrogen-doped carbon material, the metal catalytic sites are fully exposed, the lattice defects are rich, the catalytic activity is high, and it has excellent electrocatalytic CO2 reduction and oxidation performance; as an electrode material for lithium-carbon dioxide batteries, it can effectively alleviate the accumulation of discharge products during the charge-discharge stage of the battery, efficiently catalyze the oxidative decomposition of the products, and give the secondary battery a longer cycle life and lower overpotential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-gas battery electrode material preparation, and in particular to a two-dimensional nanosheet MN X -C catalyst and its preparation method and application. Background Art

[0002] With the burning of fossil fuels such as coal, oil, and natural gas around the world, carbon dioxide (CO2) emissions have grown rapidly, exacerbating the global energy crisis and greenhouse effect. CO2 emission reduction is imminent. Among them, the metal-CO2 battery process combines CO2 catalytic conversion and energy conversion-storage technology, which can reduce carbon emissions and pollution while realizing the conversion of chemical energy to green electrical energy. Compared with traditional ion batteries, M-CO2 batteries have higher specific capacity and energy density, among which lithium-CO2 batteries (LCBs) have an energy density of up to 1876Wh kg -1 , while the energy density of traditional lithium-ion batteries is only 387Wh kg -1 Therefore, LCBs batteries, as a potential power system, have great research prospects.

[0003] LCBs batteries have many advantages over traditional batteries, but in current research, the insulating discharge product Li2CO3 produced during the redox reaction of LCBs batteries will accumulate on the electrode, directly affecting the reversibility of the reaction and the cycle performance of the battery, resulting in problems such as slow reaction kinetics, high overpotential, severe polarization, and poor reversibility. Therefore, the development of low-cost, highly active, stable and durable CO2RR / CO2ER bifunctional cathode catalysts has become the key to solving the problem.

[0004] Zeolitic imidazolate framework materials (ZIFs) are a new type of porous crystalline materials that have been rapidly developed in recent years. They have the advantages of large specific surface area, high porosity, regular pores, and designable structure and performance. They can provide a large number of microporous structures, effectively avoid the aggregation of metal atoms, and provide the possibility of exposing more active sites. However, most ZIFs are unstable in structure and have poor conductivity, which makes it difficult to meet the requirements of electrode materials. Therefore, it is an important way to improve the performance of LCBs batteries by designing and modifying ZIFs precursors to prepare derived MNC materials. Two-dimensional ZIFs derivative materials not only have the advantages of ZIFs materials themselves, but also have large external specific surface area and high edge site density, which facilitates the nucleation-growth-accumulation of products and the oxidative decomposition of products, thereby improving the electrochemical performance of LCBs batteries. Summary of the invention

[0005] The present invention aims to provide a method for preparing two-dimensional ZIFs-derived materials to meet the requirements of lithium-carbon dioxide battery systems for low overpotential and long cycle life, in order to solve the problems of poor conductivity and insufficient site exposure of current catalysts, which result in slow reaction kinetics, high overpotential, severe polarization and poor reversibility of lithium-carbon dioxide batteries.

[0006] The present invention provides a two-dimensional nanosheet MN X -C catalyst preparation method, using anhydrous methanol as a medium, mixing metal salts with nitrogen heterocyclic organic ligands, and undergoing in-situ growth-template confinement-carbonization to assemble into MN X -C bifunctional catalyst; MN X -C two-dimensional nanosheets are cross-linked and interconnected, effectively shortening the electron transmission path and enhancing the electron-proton transfer capacity; large specific surface area and high stability increase the effective contact between the catalyst and the electrolyte, reactants and intermediates; strong coupling interface between transition metal and nitrogen-doped carbon material, fully exposed metal catalytic sites, rich lattice defects, high catalytic activity, and efficient and reversible CO2 absorption-desorption, which not only promotes the discharge process of lithium-carbon dioxide battery (CO2 reduction reaction, i.e. CO2RR), but also accelerates the battery charging process (CO2 oxidation reaction, i.e. CO2ER). The purpose of the present invention is mainly achieved through the following scheme:

[0007] A two-dimensional nanosheet MN X -C catalyst preparation method, characterized in that it comprises the following steps:

[0008] S1: react metal salts with nitrogen heterocyclic organic ligands to in situ grow ZIFs;

[0009] S2: ZIFs are coated with silicon hard template to obtain ZIFs@Si;

[0010] S3: Carbonize and assemble ZIFs@Si to obtain MN X -C@Si;

[0011] S4: To MN X -C@Si in the silicon hard template is etched to obtain MN X -C nanosheet catalyst.

[0012] Furthermore, the specific operation of step S1 includes the following steps:

[0013] S101: reacting a metal salt and a nitrogen heterocyclic organic ligand in anhydrous methanol at a molar ratio of 1:4 to 1:12, at a reaction temperature of 25 to 60°C, for a reaction time of 3 to 24 hours, wherein the concentration of the organic ligand in anhydrous methanol is 0.5 to 3 mol·L -1 ;

[0014] S102: Centrifuge, wash, and vacuum dry the mixed solution after the reaction to obtain ZIFs.

[0015] Furthermore, the metal salt in step S101 includes any one or more of cobalt nitrate hexahydrate, zinc nitrate hexahydrate, copper nitrate hexahydrate, chromium nitrate nonahydrate, and iron nitrate nonahydrate; the nitrogen heterocyclic organic ligand includes any one of imidazole, 2-methylimidazole, and 4,4'-bipyridine.

[0016] Furthermore, the specific operation of step S2 includes the following steps:

[0017] S201: dispersing the ZIFs obtained in step S1 in deionized water, and sequentially adding NaOH, CTAB surfactant, tetraethyl orthosilicate and anhydrous methanol in a molar ratio of 25:1 to 50:1, and stirring, wherein the volume ratio of tetraethyl orthosilicate to anhydrous methanol is 1:3 to 1:6; the concentration of NaOH in anhydrous methanol is 0.10 to 0.20 mol / L;

[0018] S202: After stirring, standing, centrifuging, washing, and drying, ZIFs@Si is obtained.

[0019] Furthermore, the specific operations of step S3 are:

[0020] The ZIFs@Si obtained in step S2 and cyanamide are placed at the middle and front ends of a tube furnace in a mass ratio of 1:1 to 8:1, and carbonized in a reducing atmosphere at a carbonization temperature of 600 to 1100°C for 3 to 6 hours to obtain MN. X -C@Si.

[0021] Furthermore, in step S3, the cyanamide includes any one of dicyandiamide and melamine; the reducing atmosphere is a H2 / Ar mixed gas with a volume ratio of 1:10 to 3:10; the tubular furnace is heated from room temperature to 350°C at a heating rate of 1 to 10°C / min and kept at a constant temperature for 2 hours; then the temperature is increased to 600 to 1100°C at a rate of 1 to 5°C / min, carbonized at a constant temperature for 3 to 6 hours, and cooled to room temperature at a cooling rate of 5 to 20°C / min.

[0022] Furthermore, the specific operation of step S4 includes the following steps:

[0023] S401: Carbonizing the MN obtained in step S3 X -C@Si is dissolved in a concentration of 2 to 5 mol·L -1 The silicon hard template is etched in a NaOH solution at a temperature of 40 to 70°C and an etching time of 10 to 24 hours;

[0024] S402: Centrifuge, wash and dry the etched product to obtain MNX -C nanosheet catalyst.

[0025] Furthermore, the two-dimensional nanosheet MN prepared by the above-mentioned preparation method X -C catalyst.

[0026] Furthermore, the two-dimensional nanosheet MN X -C catalysts as bifunctional catalysts in lithium-carbon dioxide batteries.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The present invention provides a two-dimensional MN for efficient electrocatalysis of CO2RR and CO2ER X The preparation method of ZIFs bifunctional nanosheets adopts the technology of in-situ growth-template confinement-high temperature calcination carbonization. The in-situ growth of ZIFs and the preparation process of template etching are both carried out at room temperature. The preparation process is simple and easy to implement. ZIFs are used as soft templates to retain MN X Coordination characteristics, SiO2 forms a rigid skeleton to support and confine, preventing sintering and agglomeration during carbonization; during carbonization, the internal ZIFs decompose to form MN X -C will gradually diffuse outward to form a polyhedral cavity structure, while creating surface defects, increasing the NC, especially the pyridinic nitrogen content, and X When the rigid skeleton is etched, the two-dimensional thin-sheet surface layers of the cavity polyhedron are reassembled into nanoflowers to form highly nitrogen-doped MNs. X -C Two-dimensional nanomaterials;

[0029] 2. The preparation process of this two-dimensional ZIFs-derived catalyst is simple, easy to implement and low-cost; the prepared MN X -C nanosheets are cross-linked and interconnected with each other, effectively shortening the electron transmission path and enhancing the electron-proton transfer capacity; large specific surface area and high stability increase the effective contact between the catalyst and the electrolyte, reactants and intermediates; strong coupling interface between transition metal and nitrogen-doped carbon material, fully exposed metal catalytic sites, rich lattice defects, high catalytic activity, conducive to CO2 adsorption-desorption, excellent electrocatalytic CO2RR and CO2ER performance, and great application potential;

[0030] 3.MN X -C two-dimensional nanosheets, as electrode materials for lithium-carbon dioxide batteries, can effectively alleviate the accumulation of discharge products during the charge-discharge stage of the battery, efficiently catalyze the oxidative decomposition of the products, and endow the secondary battery with a longer cycle life and lower overpotential. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a scanning electron microscope image (SEM) of Co-NC-1 prepared in Comparative Example 1 of the present invention;

[0032] Figure 2 The Co-N prepared in Example 1 of the present invention X -Scanning electron microscope (SEM) image of C;

[0033] Figure 3 The N2 isothermal adsorption-desorption curves (BET) of Example 1 and Comparative Example 1 of the present invention;

[0034] Figure 4 The XRD diffraction patterns of Example 1 and Comparative Example 1 of the present invention are shown in FIG.

[0035] Figure 5 The charge and discharge performance of the lithium-carbon dioxide battery of each embodiment of the present invention and comparative example 1;

[0036] Figure 6 The rate performance of the lithium-carbon dioxide battery of Example 1 and Comparative Example 1 of the present invention;

[0037] Figure 7 The cycle performance of the lithium-carbon dioxide battery of Example 1 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0038] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0039] Embodiment 1:

[0040] A two-dimensional nanosheet MN X -C catalyst preparation method, comprising the following steps:

[0041] S1: reacting a metal salt with a nitrogen heterocyclic organic ligand to in situ grow ZIFs; the metal salt is any one or more of cobalt nitrate hexahydrate, zinc nitrate hexahydrate, copper nitrate hexahydrate, chromium nitrate nonahydrate, and iron nitrate nonahydrate; the nitrogen heterocyclic organic ligand is any one of imidazole, 2-methylimidazole, and 4,4'-bipyridine.

[0042] Specifically, S101: Co(NO3)2·6H2O, Zn(NO3)2·6H2O and 2-methylimidazole were dissolved in anhydrous methanol, the molar ratio of the solutes was 1:1.5:20, and the concentration of 2-methylimidazole in anhydrous methanol was 2 mol·L -1 , stirred at 30°C for 6h;

[0043] S102: After reacting for 6 hours, the mixed solution was centrifuged to remove the supernatant, washed with anhydrous methanol for 3 times, and vacuum dried at 60° C. for 12 hours to obtain ZIFs; the geometric structure and size of ZIFs are related to the type and proportion of metal salts.

[0044] S2: ZIFs are coated with silicon hard template to obtain ZIFs@Si;

[0045] Specifically, S201: while deionized water is continuously and evenly stirred, the ZIFs obtained in step S1 are slowly added, ultrasonicated for 10 minutes, and then NaOH, CTAB surfactant, tetraethyl orthosilicate and anhydrous methanol are added in sequence at a molar ratio of 35:1, and stirred; wherein the volume ratio of tetraethyl orthosilicate to anhydrous methanol is 1:6; the concentration of NaOH in anhydrous methanol is 0.12 mol / L;

[0046] S202: After stirring for 30 min, the mixture was allowed to stand for 2 h, centrifuged, washed with deionized water, and vacuum dried at 80° C. for 12 h to obtain silicon-coated ZIFs (ie, ZIFs@Si).

[0047] S3: Carbonize and assemble ZIFs@Si to obtain MN x -C@Si;

[0048] Specifically, the ZIFs@Si obtained in step S2 and cyanamide are placed in the middle and front ends of the tubular furnace at a mass ratio of 3:1, and calcined at high temperature under a H2 / Ar mixed gas (volume ratio of 1:9), and the calcination temperature is increased from room temperature to 350°C at a rate of 2°C / min, and the temperature is kept constant for 2 hours to stabilize the ZIFs framework structure and avoid structural collapse due to excessive heating rate; then the temperature is increased to 800°C at a rate of 2°C / min, carbonized at a constant temperature for 4 hours, and cooled to room temperature at a cooling rate of 10°C / min to obtain Co-NC@Si.

[0049] S4: To MN X -C@Si in the silicon hard template is etched to obtain MN X -C nanosheet catalyst.

[0050] Specifically, S401: carbonizing the MN obtained in step S3 X -C@Si is dissolved in a concentration of 3 mol·L -1 The silicon hard template was etched in a NaOH solution and stirred at 50°C for 12h;

[0051] S402: After stirring for 12 hours, centrifuge to separate solid and liquid at a centrifugal speed of 5000-10000 rpm to prevent the solution from being too alkaline and corroding the glass container, then add water to dilute and filter and wash; wash with deionized water until neutral and dry for 5 hours to obtain Co-N X -C nanosheet catalyst.

[0052] In this embodiment, the CoZn-ZIFs precursor template is protected and then carbonized. Zn evaporates and escapes during the carbonization process to obtain defect-rich Co-N X -C nanosheets.

[0053] The principle of the present invention is that nitrogen-containing organic ligands such as imidazole and pyridine form zeolite-like imidazole framework compounds ZIFs with infinite periodic regular arrangement through coordination; the agglomeration between ZIFs particles caused by high temperature treatment can be effectively avoided by coating with SiO2 shell; during the carbonization process, due to the rigid framework of the external SiO2, the internal ZIFs are decomposed to form MN X -C will gradually diffuse outward to form a polyhedral cavity structure. Due to the confinement effect of the rigid skeleton, the size of the polyhedral cavity is uniform. At the same time, cyanamide decomposes to provide a nitrogen source. In the H2 reducing atmosphere, NH3 is generated by the reaction, which is beneficial to MN X The coordination mode is reconstructed to improve the NC, especially the pyridinic nitrogen content; when the SiO2 rigid skeleton is etched, the two-dimensional thin sheet surface layers of the cavity polyhedron are reassembled into nanoflowers, showing the advantages of large external specific surface area and high edge site density.

[0054] Comparative Example 1:

[0055] To further illustrate the ordered two-dimensional nanosheet MN X -C on the performance of Li-CO2 catalyst, Co-NC-1 catalyst that was carbonized without template protection was selected as a comparison.

[0056] S1: react metal salts with nitrogen heterocyclic organic ligands to in situ grow ZIFs;

[0057] Specifically, S101: Co(NO3)2·6H2O, Zn(NO3)2·6H2O and 2-methylimidazole are dissolved in anhydrous methanol, Co(NO3)2·6H2O:Zn(NO3)2·6H2O:2-methylimidazole=1:1.5:20 (molar ratio), and the concentration of 2-methylimidazole in methanol is 2 mol·L -1 , stir and react at 30°C for 6h;

[0058] S102: After reacting for 6 h, the mixed solution was centrifuged to remove the supernatant, washed with anhydrous methanol three times, and vacuum dried at 60 °C for 12 h to obtain ZIFs;

[0059] S2: Carbonization and assembly of ZIFs to obtain Co-NC-1;

[0060] Specifically, the ZIFs and cyanamide obtained in step S1 are placed in the middle and front ends of a tubular furnace at a mass ratio of 3:1, and are calcined at high temperature in a H2 / Ar mixed gas (volume ratio of 1:9). During calcination, the temperature is increased from room temperature to 350°C at a rate of 2°C / min and kept constant for 2 hours to stabilize the ZIFs framework structure and avoid structural collapse due to excessively fast heating rates; then the temperature is increased to 800°C at a rate of 2°C / min, carbonized at a constant temperature for 4 hours, and cooled to room temperature at a cooling rate of 10°C / min to obtain Co-NC-1.

[0061] Further, the Co-N prepared in Example 1 X -C nanosheet catalysts as bifunctional catalysts in lithium-carbon dioxide batteries.

[0062] The Li-CO2 assembly was carried out in a glove box with an Ar atmosphere. Lithium bis(trifluoromethanesulfonyl)imide was used as the lithium salt, tetraethylene glycol dimethyl ether was used as the solvent, the electrolyte was prepared, the metal lithium sheet was used as the negative electrode, and the glass fiber was used as the diaphragm. A total of 80 to 120 μL of electrolyte was dripped on both sides of the diaphragm. X -C nanosheet catalyst is dissolved in organic solvent and evenly sprayed on the carbon paper air diffusion layer as the positive electrode, and a porous metal shell is used as the positive electrode shell to facilitate the transportation of CO2 gas; the assembled button battery is used to measure its electrochemical performance in a high-purity CO2 atmosphere, and the test temperature is controlled at 25-30°C.

[0063] Specifically, 2 mL of anhydrous ethanol was measured and 0.5 mg of Co-N X -C catalyst, the mixed suspension was stirred evenly for 1h; sprayed on a layer of carbon paper to form the positive electrode of the battery, and dried in a vacuum drying oven at 60°C for 6h. The lithium sheet was used as the negative electrode, and 80μL of tetraethylene glycol dimethyl ether electrolyte containing lithium salt was added to form a Li-CO2 battery; as a comparison, the Co-NC-1 material prepared in Comparative Example 1 was characterized and its performance tested according to the same steps.

[0064] Figure 1 The SEM image of the Co-NC-1 material prepared by ZIFs without hard template protection in Comparative Example 1 is shown in FIG. Figure 1 It can be seen that due to the lack of hard template, the three-dimensional hollow structure of ZIFs collapsed seriously during the carbonization and calcination process, the catalytic sites were covered due to structural overlap, the effective specific surface area was reduced, the electron transfer path was blocked, and the catalytic performance was limited, resulting in the Li-CO2 battery not having an advantage in overpotential, rate, and cycle performance. These are Figure 3-7 This can be seen in Comparative Example 1.

[0065] Figure 2 The Co-N prepared in Example 1 X-SEM image of C nanosheets, from Figure 2 It can be seen that Co-N X -C nanosheets have a length of 350-500nm and a thickness of 5nm. Due to the structural defects caused by Zn escape, the original charge balance is broken, which is more conducive to the adsorption-desorption of CO2 reaction intermediates and products, and improves the rate performance, full charge-discharge performance and cycle performance of LCBs.

[0066] Figure 3 The Co-N prepared in Example 1 X -C nanosheets and the BET diagram of Co-NC-1 prepared in Comparative Example 1; Table 1 summarizes the specific surface area and pore size of Example 1 of the present invention and Comparative Example 1; Figure 3 As can be seen from Table 1, Co-N X -C nanosheets have a higher adsorption capacity for N2 than Co-NC-1 and a larger specific surface area of ​​300.85m 2 g -1 , the number of micropores is greater.

[0067] Table 1 summarizes the specific surface areas and pore sizes of Example 1 and Comparative Example 1 of the present invention;

[0068]

[0069] Figure 4 The Co-N prepared in Example 1 X -C nanosheets and the XRD patterns of Co-NC-1 prepared in Comparative Example 1. Figure 4 It can be seen that compared with Co-NC-1 in Comparative Example 1, Co-N X -C obviously has the existence of Co-N crystal plane and corresponding characteristic peaks, confirming that Co-N X successful coordination.

[0070] Figure 5 The Co-NC-1 in Comparative Example 1 and the Co-NC-1 in the embodiment X -C nanosheets with a cut-off capacity of 0.1 mAh cm -2 The first charge and discharge test diagram under Figure 5 It can be seen that the overpotential of Comparative Example 1 is 2.07V, while the overpotential of Example 1 is only 1.46V.

[0071] Figure 6 is the Co-N in Example 1 X -C nanosheets and Co-NC-1 in comparative example 1 have a cut-off capacity of 0.1 mAh cm -2 The rate performance test chart below shows Figure 6It can be seen that the charge and discharge cycles of Example 1 at various current densities are stable, the charging voltage is always maintained in the range of 4.14-4.35V, the discharge voltage drops from 3.0V to 2.65V and then returns to 2.85V, and the change of the voltage platform is less than 0.25V, showing that the Co-N X Stability of active sites; In comparison, the charge and discharge polarization of Example 1 is serious, and the charge even reaches above 4.5V. This potential can easily lead to the decomposition of the electrolyte, which has a great impact on the battery life.

[0072] Figure 7 is the Co-N in Example 1 X -C nanosheets and Co-NC-1 in comparative example 1 have a cut-off capacity of 0.1 mAh cm -2 The cycle performance test diagram below shows Figure 7 It can be seen that Example 1 can stably cycle for more than 70 cycles (>700h), demonstrating the reversibility of the material in Example 1; while the cycle of Comparative Example 1 is only about 35 cycles, and the cycle performance is far inferior to that of Example 1.

[0073] Embodiment 2:

[0074] The difference from Example 1 is that in this example, Zn(NO3)2·6H2O is replaced by Fe(NO3)3·9H2O, and other conditions remain unchanged to obtain a CoFe-NC nanosheet catalyst.

[0075] In this embodiment, the CoFe-ZIFs precursor template is protected and then carbonized to obtain the bimetallic synergistic CoFe-N X -C nanosheets, synergistically enhance the bifunctional catalysis of CO2RR and CO2ER; improve the rate performance, full charge-discharge performance and cycle performance of LCBs. Figure 5 It can be seen that the overpotential in this embodiment is 1.28V.

[0076] Embodiment 3:

[0077] The difference from Example 1 is that in this example, the obtained Co-NC@Si and dicyandiamide are placed in a tube furnace with a mass ratio of 8:1, heated at 1100°C for 6 hours under a H2 / Ar mixed gas, and cooled to room temperature to obtain a Co-N5-C catalyst.

[0078] In this embodiment, Co-N X -C nanosheet catalysts obtain a Co-N5 coordination mode with a heterofacial structure during the long-term carbonization and reconstruction process. Compared with Co-N4 in the embodiment, the charge density near Co-N5 will be enhanced, which improves the catalytic performance of CO2RR and CO2ER, and improves the rate performance, full charge-discharge performance and cycle performance of LCBs. Figure 5It can be seen that the overpotential in this embodiment is only 1.14V.

[0079] Conclusion: From Figure 1-7 It can be seen that the ordered two-dimensional nanosheet MN prepared by the present invention X -C has a large external specific surface area and a high density of edge sites, which effectively improves the reaction kinetics and proton-electron transfer capacity of the catalyst, is conducive to the nucleation-growth-accumulation and oxidative decomposition of the product, and exhibits excellent electrochemical performance. X -C nanosheet catalyst, compared with traditional ZIFs-derived materials, the overpotential of Li-CO2 batteries is reduced and the cycle performance is significantly improved.

[0080] Several highly efficient two-dimensional nano MNs were prepared in the above examples. X -C catalyst realizes the dual-function catalysis of charge and discharge of Li-CO2 battery, providing an effective method for the conversion and utilization of CO2.

[0081] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A two-dimensional nanosheet MN X -C catalyst preparation method, characterized in that, The following steps are involved: S1: react metal salts with nitrogen heterocyclic organic ligands to in situ grow ZIFs; S2: ZIFs are coated with silicon hard template to obtain ZIFs@Si; S3: Carbonize and assemble ZIFs@Si to obtain MN X -C@Si; S4: To MN X -C@Si in the silicon hard template is etched to obtain MN X -C nanosheet catalyst; The specific operations of step S1 include: S101: reacting a metal salt and a nitrogen heterocyclic organic ligand in anhydrous methanol at a molar ratio of 1:4 to 1:12, at a reaction temperature of 25 to 60°C, for a reaction time of 3 to 24 hours, wherein the concentration of the organic ligand in anhydrous methanol is 0.5 to 3 mol·L -1 ; S102: centrifuging, washing, and vacuum drying the reaction mixture to obtain ZIFs; The specific operations of step S2 include: S201: dispersing the ZIFs obtained in step S1 in deionized water, and sequentially adding NaOH, CTAB surfactant, tetraethyl orthosilicate and anhydrous methanol in a molar ratio of 25:1 to 50:1, and stirring; wherein the volume ratio of tetraethyl orthosilicate to anhydrous methanol is 1:3 to 1:6; and the concentration of NaOH in anhydrous methanol is 0.10 to 0.20 mol / L; S202: After stirring, standing, centrifuging, washing, and drying to obtain ZIFs@Si; The specific operation of step S3 includes placing the ZIFs@Si obtained in step S2 and cyanamide at a mass ratio of 1:1 to 8:1 at the middle and front ends of a tube furnace, respectively, and carbonizing them under a reducing atmosphere at a carbonization temperature of 600 to 1100°C for a carbonization time of 3 to 6 hours to obtain MN X -C@Si; The specific operations of step S4 include: S401: Carbonizing the MN obtained in step S3 X -C@Si is dissolved in a concentration of 2 to 5 mol·L -1 The silicon hard template is etched in a NaOH solution at a temperature of 40 to 70°C and an etching time of 10 to 24 hours; S402: Centrifuge, wash and dry the etched product to obtain MN X -C nanosheet catalyst; The metal salt in step S101 includes any one or more of cobalt nitrate hexahydrate, zinc nitrate hexahydrate, copper nitrate hexahydrate, chromium nitrate nonahydrate, and iron nitrate nonahydrate; the nitrogen heterocyclic organic ligand includes any one of imidazole, 2-methylimidazole, and 4,4'-bipyridine; In step S3, the cyanamide includes any one of dicyandiamide and melamine; the reducing atmosphere is a H2 / Ar mixed gas with a volume ratio of 1:10 to 3:10; the tubular furnace is heated from room temperature to 350°C at a heating rate of 1 to 10°C / min and kept at a constant temperature for 2 hours; then the temperature is increased to 600 to 1100°C at a rate of 1 to 5°C / min, carbonized at a constant temperature for 3 to 6 hours, and cooled to room temperature at a cooling rate of 5 to 20°C / min.

2. The two-dimensional nanosheet MN prepared by the preparation method according to claim 1 X -C catalyst.

3. The two-dimensional nanosheet MN as claimed in claim 2 X -C catalysts as bifunctional catalysts in lithium-carbon dioxide batteries.

Citation Information

Patent Citations

  • Vertical graphene loaded carbon nano tube composite electrode material and preparation method thereof, and application of composite electrode material in all-solid-state zinc-air battery

    CN110350206A

  • Method for preparing metal monatomic electrocatalytic oxygen reduction catalyst through confinement space

    CN112736259A

  • Lithium-sulfur battery positive electrode material as well as preparation method and application thereof

    CN114420916A